Marine Invertebrates of McMurdo Sound - Marsh, Adam G. (IEDA: US Antarctic Program Data Center, 2008)
Abstract: Although we envision the coastal margins of Antarctica as an extreme environment challenging to the existence of life, there are many marine invertebrates that are adapted to live and thrive under the sea ice. For two field seasons, the SCUBA diving activities of this project routinely involved photographing these animals in all the dive locations as a way to document what we observed as the dominant organisms at each site. Ice diving is very strenuous for humans, and often the constraints of managing the work on a dive, monitoring air reserves, tracking proximity to the dive hole, and the 50 minute exposure to subfreezing temperatures limits a divers ability to "catalog" observations that are not essential to the current dive plan. The photographs archived here have provided the project's dive team with the ability to "debrief" following a dive and more or less reenact the dive by moving through the photograph images. Studying these images often served as a visual trigger for divers to recall more specific observations and in many cases details in the photographs were captured without the photographer (A. Marsh) realizing that they were there (such as small, cryptic species hiding in a shadow until the strobe light fires for the photo, illuminating these secondary subjects). These photographs are intended to serve as a record of what organisms we encountered in the McMurdo Sound area in 2004 and 2005. All photographs were taken with a Nikon D-70 in a polycarbonate underwater housing using either a 18 mm (wide) or 60 mm (macro) lens.